The weirdstone of Brisingamen - Garner, Alan, 1934- (London : HarperCollins Children's Books, 2010)
A young girl and her brother are catapulted into a battle between good and evil for possession of a magical stone of great power that is contained in her bracelet.
6.3
5-8.
5-8
Keywords: Fantasy; Magic; Magic -- Fiction; Fantastic fiction